Centro de atención residencial para niños en estado de abandono ubicado en Jesús María - Salas Morales, Christian Paolo (2022)
The topic of research is a Residential Shelter (CAR) for children and teenagers (NNA) in a current state of abandonment, rethinking the conventional model of shelters dedicated to infants, through a proposal with an architectural approach towards a playful aspect and located in the district of Jesus Maria. The main objective of the research is to design a shelter based on the profile of its main users: children and teenagers, analysing the forms of site and design of minor housing which are currently applied, how important family upbringing is in child development and how to highlight the family as a composition cell in the project. Additionally, it is expected to use the most characteristic activity of the children, the game, as an alternative learning method and resource in order to encourage the youngsters to be able to create their own spaces according to the needs and interests of the childhood stage they are experiencing in the present. The project will have a playful approach, one that can be applied in the shelter design process, that also promotes creativity and both personal and collective development of minors through various assisted play spaces, which are presented in different areas and levels along the building. These characteristics are achieved through the presence of alternative play and learning setting zones, flexibility in the internal distribution and exterior housing organization, the incorporation of meeting spaces in between the routes, the stimulation with natural environments both indoors and outdoors and the diversity of playing areas available at each level of the project. Finally, a playful shelter is summarized as one that promotes the creative ability of the children and at the same time can attend to the affective and spatial needs of the diverse under-age groups in an organized and systematic way represented in the project